Anticorpos anti-Leishmania spp. em equinos de áreas do Rio Grande do Sul com diferentes classificações epidemiológicas quanto à transmissão de leishmaniose viscera - Daudt, Gabriela de Freitas (2023)
Protozoans of the Leishmania genus are the etiological agent of leishmaniasis that are maintained in wild and urban reservoirs. The importance of studying leishmaniosis in horses is due to their closely contact with humans, as dogs, and to being able to develop clinical disease. Considering that the data on Leishmania spp. detection in horses in the South Brazil is limited and the studies suggesting that horses participate in the leishmaniasis epidemiology, this dissertation aimed to investigate the presence of anti-Leishmania spp. antibodies in serum samples of horses from areas with different occurrence of visceral leishmaniasis (VL) transmission. Serum samples of 436 horses were diluted (1:40) and tested by Indirect Fluorescent Antibody Test (IFAT) for antibodies against Leishmania spp. using a Leishmania infantum strain as antigen. Samples were classified according to the origin (visceral leishmaniasis transmission or silent areas) and housing type and purpose of the horses (traction or farming). Antibodies anti-Leishmania spp. were detected in 9,17% of the samples. The highest detection frequency was reported in animals from transmission areas (29.41%), followed by the silent areas (6.49%). The frequency of antibodies detection was 9,46% and 8,8%, to traction and to farming horses, respectively. These results revealed that Leishmania spp. is circulating in both evaluated regions. It also suggests that horses may act as reservoirs, but further studies are required to clarify the pathogenesis and epidemiology of Leishmania spp. infection in horses and their role in spreading leishmaniasis between humans and animals.